The association between sharing something difficult on social media and mental well-being among adolescents. Results from the “LifeOnSoMe”-study - Kysnes, Bjarte; Hjetland, Gunnhild Johnsen; Haug, Ellen; Holsen, Ingrid; Skogen, Jens Christoffer (Frontiers in Psychology, 2022)
Introduction Social media use is part of everyday life for adolescents. Over the last decade, concerns about the potential negative effects of social media use on mental health and well-being has been raised. Possible positive effects of social media use have to a lesser extent been explored. However, some studies have found associations between social support on social media and well-being. Self-disclosing thoughts and feelings on social media might provide social support and positively affect well-being. The current study aimed to explore adolescents’ experiences with sharing something difficult on social media and the association with well-being. Methods The survey data in this cross-sectional study were collected from a sample of 2023 adolescents from senior high schools (mean age 17.4, 55.6% females). Mental well-being was measured using the Warwick-Edinburgh Mental Well-being scale (WEMWBS). Multiple linear regression adjusting for age, gender, social media frequency/duration of use, and the number of close friends was used to explore the association of sharing something difficult on social media and mental well-being. Results The findings indicated that sharing something difficult on social media, either with a few friends/family members or in a public post, was associated with lower well-being. Perceived social support (easier to talk about, received support, positive experience) after sharing something difficult was associated with higher well-being. Females reported sharing something difficult more than boys, but no interaction effect of gender was found in the associations between private or public sharing and well-being. Discussion The results indicate that social media can serve as a supportive environment for adolescents. Future research may want to explore additional aspects of adolescents’ social media use, sharing, and well-being, such as differences in public and private sharing. Such contributions will increase the knowledge base of optimal ways to seek social support through social media.